Respuesta :

Space

Answer:

x = -6

Step-by-step explanation:

Step 1: Write out equation

5x + (-2) = 6x + 4

Step 2: Simplify

5x - 2 = 6x + 4

Step 3: Subtract 5x on both sides

-2 = x + 4

Step 4: Subtract 4 on both sides

-6 = x

Step 5: Rewrite

x = -6

Answer:

x = -6

Step-by-step explanation:

[tex]5x+(-2)=6x+4[/tex]

Open the parenthesis

[tex]+(-2) =-2\\\\5x -2 =6x+4[/tex]

Collect like terms and simplify

[tex]5x-6x =4+2\\-x =6[/tex]

Multiply through by -1

[tex]-1(-x)=-1(6)\\\\x = -6[/tex]